PENGARUH ENVIRONMENTAL PERFORMANCE PADA ECONOMIC PERFORMANCE DENGAN ENVIRONMENTAL DISCLOSURE SEBAGAI PEMEDIASI (Studi Empiris Pada Perusahaan Manufaktur Dan Pertambangan Yang Terdaftar Di Bursa Efek Indonesia) - Daat, Sylvia Christina; Pangayow, Bill J. C. (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2020)
This research was motivated by the development of the direction of accounting research on greenÂ accounting issues. Companies that want a going concern operation must pay attention to 3P, namelyÂ profit as profit, people where companies must pay attention to the welfare of the community, and theÂ planet is the companyâ€™s contribution to the environment. Therefore, this study tries to find empiricalÂ evidence on the influence of several environmental variables, including the environmentalÂ performance of the company and disclosure of the companyâ€™s environmental management activitiesÂ to the public on the sustainability of the company with increasing economic (financial) performanceÂ of the company. The results of the study using the Structural Equation Model (SEM) approach withÂ the Partial Least Square (PLS) method using Software WarpPLS 5.0 provide empirical evidence thatÂ the companyâ€™s Environmental Performance influences the companyâ€™s Economic Performance, butÂ does not provide empirical evidence that environmental disclosure company as a conncecting variabel or mediating the relationship of environmental performance with economic performance